Doric : the dialect of North-East Scotland - McClure, J. Derrick (Varieties of English around the world. Text series ;, 2002)
The dialect of North-East Scotland, one of the most distinctive and best preserved in the country, survives as both a proudly maintained mark of local identity and the vehicle for a remarkable regional literature. The present study, after placing the dialect in its historical, geographical and social context, discusses in some detail a selection of previous accounts of its distinctive characteristics of phonology and grammar, showing that its shibboleths have been well recognised, and have remained consistent, over a long period. Passages of recorded speech are then examined, with extensive u.